C39. Ductus Arteriosus Stenting: A Promising and Life Saving Procedure for Ductal-Dependent Pulmonary Blood Flow. (23rd November 2021) - Permitasari, D A; Priyatno, A; Ayukusuma, A R; Andini, A R; Christina, M; Susilawati, M
Abstract: Background: Duct-dependant congenital heart disease in newborn presents as a life-threatening emergency and the survival depends on patency of the ductus arteriosus. Stent implantation into ductus arteriosus has been proposed as non-surgical management for critical congenital heart disease with duct-dependent. Case Summary: We present full-term newborn babies who had critical congenital heart disease with ductal-dependent pulmonary blood blow and successfully managed with ductal stenting. Patient A, a 13-days-old male had Tetralogy of Fallot-Pulmonary Atresia and restrictive Ventricular Septal Defect (VSD). Patient B, a 3-days-old male had Pulmonary Atresia-Intact Ventricular Septum (PA-IVS) with Patent Foramen Ovale (PFO). Patient C, a 5-days-old female had Tricuspid Atresia with restrictive VSD and multiple congenital anomaly. Patient D, a 2-days-old female had PA-IVS with PFO stretch. Prostaglandin-E1 infusion was started at first and stop 6 hours prior to the procedure. Ductus arteriosus stenting using drug-eluting stent and femoral artery approach was successful in all 4 patients. All patient had improvement of oxygen saturation and good post-procedure outcome. Discussion: Ductal stenting in patient with duct-dependent pulmonary circulation appears to be an alternative to surgery. It provides a bridging palliation in cyanotic congenital heart disease until the time of definitive surgery. Stenting of ductus arteriosus is feasible and safe with good result, thus early recognition and timely management are important to save the life.